Sejarah dan etnisiti Muslim di Chiang Mai - Farid Mat Zain , (Penerbit Universiti Kebangsaan Malaysia, 2003)
Chiang Mai is one of Thai northern states, it is sparsely populated by the Muslim. This study is aimed at examining the life of the Muslim minority in the Buddith majority. Likewise, it is to identify how far Islamic norms and virtues are being observed in daily life. Of the Muslim minority, there are two main groups, i.e; Indo-Pakistan origin and Sino-Yunnan origin. Retrospectively, both people, who imigrated into Chiang Mai have shaped the Islamic image and attitude. Apart from that, they are able to maintain their distinguished identity and culture, widening interaction gap between them and newly muslim converts. To sum up, the Muslim society of Chiang Mai do contribute to the development and prosperity of the state of Chiang Mai